사용자 선호기반 웨어러블 디바이스의 수용성 연구: 스마트워치를 중심으로 - 김민석; 김원준; 김민기; 강재원; Kim, Minseok; Kim, Wonjoon; Kim, Minki; Kang, Jae Won (한국콘텐츠학회 논문지, 17(9), 2017)
Despite consumers' increasing awareness and interests in innovative wearable devices, the sales growth has been stagnant. To analyze this phenomenon, we investigate consumer preferences for various innovative features embedded in wearable devices. Conducting conjoint analysis on smartwatches, we empirically show that the curse of innovation can occur when the consumer's expected utility from the smartwatch falls short of his/her psychological cost associated with behavior change from smartwatch usage. Therefore, our findings provide managerial implications on the R&D strategy for new technologies and more importantly on the marketing strategy easing consumers' resistance to highly innovative products. 다양한 기능을 제공하는 웨어러블 디바이스에 대한 대중의 인지 및 관심은 크게 증가하였으나, 정작 실제 판매 성장률은 정체되는 현상이 관찰되고 있다. 본 논문은 이러한 웨어러블 디바이스의 확산정체현상을 분석하기 위해 향후 스마트워치에 내장될 서비스 기술들에 대한 소비자의 선호를 컨조인트 분석을 통해 파악하였다. 또한, 스마트워치의 각 서비스별 소비자 지불의사금액을 도출하여, 스마트워치 제품별 간접효용과 이에 기반한 상대적 소비자 수용률을 예측하였다. 그 결과 신기술 사용으로 얻는 기대효용보다 스마트워치 착용이 야기하는 새로운 행동양식의 변화로 인한 심리적인 비용이 클 경우, 소비자들이 구매를 주저하여 혁신적인 제품의 확산이 저해되는 소위 '혁신의 저주'가 스마트워치 시장에서도 나타날 수 있음을 확인하였다. 이와 같은 분석결과는 웨어러블 디바이스 기술개발 계획 수립과 같은 기술전략 뿐만 아니라, 제품출시 및 판매가격 설정 등 마케팅 전략에 대한 실무적 시사점을 제공한다.